A174 A RETROSPECTIVE REVIEW OF CO-PRESCRIBING DIFECT ACTING ANTIVIRALS WITH HMG-COA REDUCTASE INHIBITORS IN HEPATITIS C INFECTED PATIENTS IN A VIRAL HEPATITIS CLINIC. (1st March 2018) - DeVreese, L; Giguère, P; Cooper, C
Abstract: Background: Direct Acting Antiviral (DAA) therapy for the treatment of hepatitis C virus (HCV) has led to improvements in the efficacy, safety and tolerability of HCV management. However, managing drug-drug interactions between NS5A inhibitors and HMG-CoA reductase inhibitors (statins) remains a challenge in clinical practice. Aims: The aim of this study was to assess the safety and tolerability of either continuing or discontinuing statins while on NS5A-based DAA therapy. By retrospectively evaluating statin use in our HCV clinic patients, we aspired to gain a better appreciation of how to safely manage patients presenting on concomitant therapy. Methods: A retrospective chart review at The Ottawa Hospital Viral Hepatitis Program's clinic was performed to 1) assess the number of statin-treated patients on NS5A inhibitor based HCV treatment and 2) to assess the safety and tolerability of either continuing or discontinuing statins while on NS5A inhibitor DAA therapy, measured by the incidence of statin related myopathies and vascular events. Results: 29/165 (17.8%) of patients pursing NS5A inhibitor therapy presented on a statin at baseline. Six out of 29 (20.7%) discontinued their statin prior to treatment, 10/29 (34.5%) continued on baseline doses and 13/29 (44.8%) were on a decreased dose. All patients on co-therapy were on low doses of statins with none exceeding 25% of the suggested maximum daily statin dose. During co-therapy, one patient experienced stomach cramping and no patients discontinued their statin during DAA therapy. Of those discontinuing statins prior to starting treatment, no patients developed vascular complications. One patient remaining on statin therapy suffered a myocardial infarction. Conclusions: Although prescribing practices were not uniform, the majority of patients on a baseline statin were continued on statin therapy throughout NS5A inhibitor-based HCV therapy. Co-administration of low-dose statins with NS5A inhibitors appeared to be well tolerated resulting in no apparent or serious statin-related adverse effects, despite the theoretical risk for DDIs. While co-therapy was reassuringly well tolerated, practitioners must continue to weigh the benefits and risks of co-administering statin therapy on a case-by-case basis. The addition of larger, prospective studies may help to better characterize the implications of pursuing co-therapy and provide further guidance to clinicians managing these complex patients. Funding Agencies: None